Le first lady del Quirinale e la Costituzione : Contributo allo studio del ruolo costituzionale delle consorti e delle supplenti consorti del Presidente della Repubblica nell’ordinamento italiano (Società e diritti, 2022)
AbstractIn Italy, there is no official role for the presidential first lady, however the history of the Republic indicates many different ways of playing the role of the President's wife. Alongside a historical and institutional reconstruction, and a specific investigation on the title and treatment due to the President's wife, the contribution aims to identify the common lines of the activities of the various presidential first ladies, investigating in particular their role according to the Constitution, beyond the interpretation given by each person who has played their role over time. A role that is not purely formal and ceremonial, but helps to outline the role of the President himself.